w PERANCANGAN WISATA PEMANCINGAN MONGAILA DI DESA POHUWATO TIMUR KABUPATEN POHUWATO DENGAN PENDEKATAN ARSITEKTUR VERNAKULAR: PERANCANGAN WISATA PEMANCINGAN MONGAILA DI DESA POHUWATO TIMUR KABUPATEN POHUWATO DENGAN PENDEKATAN ARSITEKTUR VERNAKULAR - Savitri, Siti Asiatul; Nurmiah, Nurmiah (Venustas, 2023)
This final project aims to analyze, plan and design a design concept for Mongaili Fishing Tourism in East Pohuwato Village, Pohuwato Regency with a Vernacular Architecture Approach with the main function as a forum for new Fishing Tourism for Pohuwato Regency. In Pohuwato District, regional income is not only from the agricultural sector, but also the fisheries sector, making fishermen a permanent source of income. According to survey data, there are very high interest rates for fishing enthusiasts who can be explored along the Pohon Cinta Beach. There are enthusiasts for fishing. This makes a strong reason. for a plan for a Mongaili Fishing Tour. This design was carried out in Pohuwato Regency by collecting data related to the design of the Mongaili Fishing Tour. Structural Design of the Mongaili Fishing Tourism Area, as well as direct observation to determine the condition of the facilities around the recreation area for visitors to be used as material for analysis in the design of Mongaili Fishing Tourism in Pohuwato Regency with a Vernacular Architecture Approach. The form of structuring and development of this area is influenced by several other things, namely the results of site analysis which gives rise to zoning at the site which is then adjusted to the conditions and ecological concept of the area that will be applied to the area. It is hoped that visitor activities will not focus on just one activity area.. Keyword: Architecture Vernacular, Fishing, Tour.